Does Profitability Matter? The Dual Role of ROA and ROE in the ESG–Firm Value Relationship - Yandi Suprapto; Isnaini Nuzula Agustin; Ayesha Antonia Putri (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2025)
Purpose: This study investigates the relationship between Environmental, Social, and Governance (ESG) performance and firm value, with profitability—measured by Return on Assets (ROA) and Return on Equity (ROE)—serving as the moderating variable.Method: Data were collected from companies listed on the Indonesian Stock Exchange (IDX) over five years (2019-2023). Control variables include firm size, firm age, and leverage. This study employs a quantitative approach, utilizing panel data regression on 209 firm-year observations from IDX-listed companies. Tobin’s Q serves as a proxy for firm value, while the ESG score is the independent variable, moderated by profitability.Result: The findings indicate that ESG performance positively affects firm value in the base model. However, this effect turns negative when profitability is included as a moderator. Notably, the interaction term ESG*ROE has a significant positive effect, suggesting that higher profitability (as reflected by ROE) enhances the positive impact of ESG on firm value. In contrast, ROA does not exhibit a significant moderating effect.Practical Implications for Economic Growth and Development: This study underscores the importance of integrating sustainability efforts (ESG) with strong financial performance to create long-term value. This insight is crucial for policymakers and investors aiming to promote responsible business practices and sustainable economic development.Originality/Value: This study examines the moderating role of profitability—specifically ROA and ROE—in the relationship between ESG performance and firm value. By focusing on an emerging market context, this research offers insights on how different dimensions of profitability influence the ESG–firm value nexus.